Acremotins A–D, peptaibiotics produced by the soil-derived fungus Acremonium persicinum SC0105. (November 2018) - Wang, Chen; Wu, Ping; Yao, Lei; Xue, Jinghua; Xu, Liangxiong; Li, Hanxiang; Deng, Wangqiu; Wei, Xiaoyi
Abstract Four new peptaibiotics, acremotins A–D (1 –4 ) featuring threeα, α -dialkylated amino acid–imino acid motifs and an unreduced C-terminal residue, along with the known peptaibiotic XR586 (5 ) were isolated from the solid cultures of the soil-derived fungusAcremonium persicinum SC0105. Their primary structures were characterized by detailed analysis of the HRESIMS/MS fragmentation pattern combined with comprehensive interpretation of the 1D and 2D NMR spectroscopic data. The absolute configurations of amino acid residues were determined by the advanced Marfey's method. Sequence alignment result shows that1 –4 are closely related to zervamicin IIB and emerimicin IIA, thus belong to peptaibiotic subfamily-3 (SF3). The three-dimensional (3D) structure of4 was established by theoretical conformational analysis using theab initio density functional theory (DFT) method, which, together with the CD spectrum, indicated an amphiphilic and helical structure for4 .1 –5 actively inhibited the growth of gram-positive bacterial pathogens, and amongst them4 was the most potent compound showing MIC of 12.5 and 6.25 µg/ml againstS. aureu and MRSA strains, respectively.1 –5 were also cytotoxic against three human cancer cell lines with IC50 ranging from 1.2 to 21.6 μM.